A case study on demolition work in Malaysia / Mohd. Zafarizan Mohd. Sarbini - Mohd. Sarbini, Mohd. Zafarizan (Faculty of Architecture, Planning and Surveying, 2009)
Turning the attention towards the present time, we can note the situation now is of somewhat different. An apparent observation can be made in terms of infrastructure development. Road networks of the past are no longer capable of sustaining the substantial increase of vehicle volume. There has been extensive upgrading and buildings of new highway ease traffic congestion. These works required land acquisitions from private parties as well as involved a considerable amount of demolition project. An ideal case study to illustrate construction of the Lumba Kuda Flats in Johor Bahru. Due to the alarmingly decreasing land for construction nations are calling for the use of developed sites and conversions of existing buildings to meet current demands. Therefore on a broad spectrum, demolition can be predicted to be playing as a role major in future nation building. The industry which was previously unknown and termed unsophisticated has finally found itself in the limelight with greater appreciation.